مدى استخدام المعلومات المحاسبية في التخطيط والرقابة واتخاذ القرارات دراسة حالة مصرف ليبيا المركزي ومصرف الوحدة - بوبكر فرج شريعة (Scientific Journal of University of Benghazi, 2021)
Purpose: The aim of this study is to know the extent of utilisation of accounting information prepared by accounting information system in Al-wahda Bank in decision-making, planning and control, with a special focus on Al-wahda Bank and the central bank of Libya. Design/methodology/approach: to achieve the aim of this study, it was necessary to ensure the availability of qualitative characteristics of accounting information, which were prepared by accounting information systems in Al-wahda Bank. The case study methodology is used to develop two case studies. One organisation is examined as a provider of information (Al-wahda Bank), and another, The Central Bank of Libya, as a user. A variety of data collection methods are used, including semi-structured interviews, observations, and document analysis in order to make data triangulation possible. Findings: the study concluded that there is a benefit from the information prepared and provided by the accounting information system in Al-wahda Bank to Central Bank of Libya. However, there are several exceptions in the opinions of some participants. Moreover, The study indicated that this information provided from Al-wahda Bank has the qualitative characteristics of information in the point of view of most participants. Research limitation/implications: Whilst this study demonstrates the extent of the use of accounting information in decision-making, planning and control, it has focused only on two organizations within Libya. Consequently, even though organizations have many similarities, the generalizability of this study is limited. It would be useful to replicate the study in other organizations within Libya. The use of different research methods, for example, a larger style of survey or a different kind of qualitative study, could provide different or additional insights. Originality/value: this study represents a good addition, as it indicated that the methodology used in the study may give more profound and detailed results and thus may open up future prospects for other studies in this field.